The Correlation Between Post Traumatic Stress Disorder (PTSD) With The Behavior Response (BR) Of The School Age Children After The Eruption of Mount Kelud at Puncu Village Puncu Subdistrict Kediri Regency - Asrori, Riswan; Novita Ana Anggraini; Alfian Fawzi (Universitas STRADA Indonesia, 2016)
Natural disasters were a matter that was never expected. Coming disaster of humans caused by psychological shock, especially of children. The children who experience a traumatic event could certainly have post-traumatic stress disorder. The purpose of this research was to identify the presence of post-traumatic stress disorder, behavior response and to analyze the correlation between post traumatic stress disorder with the behavior response of the school-age children after the eruption of Mount Kelud. This research was a descriptive correlational cross sectional design. A sample of 227 school age children were taken by purposive sampling technique in the village Puncu subdistrict district Puncu Kediri. The research instrument used in the form of a questionnaire consisting of 22 questions related to post traumatic stress disorder and 5 questions with regard to response behavior. Results of research showed most respondents with post traumatic stress disorder were as many as 117 children (51.5%), response behavior light as 121 children (53.3%). Based on statistical tests Spearman rho is obtained p value =0.000<(0.05). This means that H0 is rejected, there is post traumatic stress disorder with response behavior in school aged children after the eruption of mount kelud in rural subdistrict Puncu puncu Kediri district. By looking at the value of r=0.748 which means a close relationship partner. Someone who gets stimulation will exhibit symptoms, so that psychological rewards and bring the response behavior. It is recommended for children who have post traumatic stress disorder and response behavior to be given treatments such as psychotherapy of pharmacotherapy.